CFD Cook‐Off Simulation and Thermal Decomposition of Confined High Energetic Material. Issue 5 (16th April 2015) - Asante, Daniel O.; Kim, Shinhyuk; Chae, Jooseung; Kim, Hyounsoo; Oh, Min
Abstract The handling, storage and safety before deployment of explosives are major key issues that confront the ammunition industry. Precautions have to be taken not to cause premature detonations and fatal accidents by studying their thermal behaviour. Research has been conducted to investigate the thermal stability of some secondary explosives such as RDX, HMX and TNT and their response to thermal stimuli. For the fact that real experiment which involves large amount of explosives can be potentially dangerous, cook‐off numerical simulation and experiment has been regarded as the best method to analyse such thermal behaviour of explosives. Prominent among these researches involve experiment and numerical analysis such as ODTX, SITI, and DDT experiments. In this work, numerical CFD simulation will be executed for the thermal behaviour of TNT including cook‐off and thermal decomposition. The heating rates were varied for both slow and fast cook‐off cases. In view of these thermal decomposition reactions which mainly consist of kinetic parameters were factored in the numerical simulation as well as the critical thermodynamic physical properties. To effectively handle the reactions, UDF was employed. Attention was paid on the melting time to ignition of explosive, the location likely for ignition occurrence, as well as temperature distribution in the course of the heating process. CFD simulation results showed that the location of ignition was around the supplementary charge.